Changes to the micro-architecture and material properties of the human clavicle and rib in ontogeny - McGivern, Hannah L (Cranfield University, 2019)
The detrimental effects of ageing on the human skeleton are universally resonant. With increase in age, an increased fragility at the macroscopic scale is observed in bone, which is indicative of changes that occur at different levels within the heterogeneous and complex, hierarchical arrangement of this biological composite. In spite of that, a comprehensive understanding of ageing characteristics in the medial clavicle is largely missing from the literature. The seminal research currently available concerns developmental markers such as morphological alterations to shape and structure, which are capped at the point of skeletal maturity. Estimating age-at-death continues to be one of the most challenging responsibilities for forensic anthropologists when compiling a biological profile for unidentified skeletonised human remains (most especially following the maturation of the skeleton). The medial clavicle and sternal rib ends are fundamental to age estimation; the former is the last bone to fuse in the human skeleton making the development ideal for estimating age when the remainder of the skeleton has completed epiphyseal fusion, and the latter are easily accessible during routine autopsy. Current methods which utilise these skeletal sub-regions are primarily qualitative and rely on the expert interpretation of subjective traits which relate to broad and descriptive phase categories. There is a need to go beyond using morphological biomarkers currently employed in forensic anthropology. The introduction of new, quantitative techniques is therefore fundamental to addressing the following unanswered question: what significant, ontogenetic changes occur beyond the macro-scale which can be utilised for generating multivariate age prediction models for the clavicle and rib? In order to address this question, the primary research aim for this research was to characterise statistically significant (p0.7 to effectively predict age-at-death. This novel approach addresses disciplinary norms through the application of micro-computed tomography (µ-CT), nanoindentation and the combined diagnostic power of two thermo-analytical techniques (DSC-TGA) to elucidate agerelated changes in a sample of 161 cadaveric specimens from 58 donors at a scale beyond what has thus far been presented in the literature. Accordingly, a series of associated hypotheses were devised concerning the individual constituent parts, which altogether contribute to the physical manifestiations of age and form the complex arrangment of bone, using each of these techniques. The effect of the size of the sample has also been considered. The age range of the sample in question (12-59 years) focuses on a division of the age spectrum which has received less attention in previous studies, particularly in comparison to study groups which have primarily comprised of elderly individuals. Firstly, a non-destructive assessment of the morphometric characteristics of the trabecular bone located in the medial end of the clavicle was implemented using micro-computed tomography (µ-CT) to test for statistically signficant (p0.7 which is indicative of a strong model. iv Additionally, the value of adopting a multi-method system was illustrated using Principal Component Analysis (PCA) which revealed the extent to which principal components (namely HVIT, EIT, percentage loss of organic weight [Or%] and final percentage weight of mineral phase [Ash%]) were contributing to clustering patterns associated with age. These findings explore the research hypothesis which concerns the identification of changes to clavicle and rib physiology and mechanical behaviour in ontogeny; details that will hold significant value in medico-legal cases for age-atdeath estimation. This research also addresses set objectives concerned with the development of easily reproducible and accurate methods of age-at-death estimation using the medial clavicle and sternal end of the sixth rib without specialist anthropological expertise. The results presented also contribute to basic knowledge of mechano-biology for micro- and nano-structures that influence fracture risk at the organ level, which is of interest to clinicians in orthopaedic biomechanics and is also vital to other sectors. For example, the automotive industry can use such data to establish whether age-related changes to the structure and material composition of these bones lessens the failure threshold and mechanical behaviour of the chest in vehicle collisions. This information in turn could also contribute to the improvememt of automotive safety designs.